2017
DOI: 10.1103/physrevlett.119.265502
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Pair Correlation Function in the Dynamical Transition Predicted by Mode Coupling Theory

Abstract: In a recent study, we have found that for a large number of systems the configurational entropy at the pair level S_{c2}, which is primarily determined by the pair correlation function, vanishes at the dynamical transition temperature T_{c}. Thus, it appears that the information of the transition temperature is embedded in the structure of the liquid. In order to investigate this, we describe the dynamics of the system at the mean field level and, using the concepts of the dynamical density functional theory, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 48 publications
3
43
0
Order By: Relevance
“…It has also been suggested that the crossover temperature T c might be inferred from the T variation of S ex . 304,306 It would be an invaluable advance to the GET to have an alternative thermodynamic-based approach for calculating T A , and we plan to test this proposal against independent estimates of T A for our polymer model in the future. Over time, we hope to see the various 'pieces' of the entropy theory of glass formation to grow together to form a highly predictive and validated framework from theoretical, computational, and experimental perspectives.…”
Section: Rosenfeld and Excess-entropy Scalingmentioning
confidence: 99%
“…It has also been suggested that the crossover temperature T c might be inferred from the T variation of S ex . 304,306 It would be an invaluable advance to the GET to have an alternative thermodynamic-based approach for calculating T A , and we plan to test this proposal against independent estimates of T A for our polymer model in the future. Over time, we hope to see the various 'pieces' of the entropy theory of glass formation to grow together to form a highly predictive and validated framework from theoretical, computational, and experimental perspectives.…”
Section: Rosenfeld and Excess-entropy Scalingmentioning
confidence: 99%
“…The two potentials, the LJ and WCA, have same repulsive core but different attractive part; the LJ has an attractive tail while the WCA has no attraction. These models therefore offer an ideal benchmark for evaluating the role of repulsive and attractive interactions on the local structural order and on slowing down of dynamics of glass-forming liquids, and have been studied extensively over last several years [5,6,[8][9][10][11][12][13][14][15][16][17][18][19][20][21]. We compare results of the two systems and identify causes that give rise a large difference in their local structural order and dynamics at lower liquid-like densities but almost identical results at sufficiently large densities.…”
Section: Introductionmentioning
confidence: 99%
“…Local structure analysis using topological cluster classification [29] and Voronoi face analysis [12] also point to subtle structural difference. Using the configurational entropy as the thermodynamic maker via the Adam-Gibbs relation [30], Banerjee et al [16][17][18] showed that the difference in dynamics of the WCA and LJ systems is due to difference in their configurational entropy. These results prompt one to ask whether a unified physical framework exists to understand the structure and dynamics and their relationship for systems such as the LJ and WCA glass forming liquids.…”
Section: Introductionmentioning
confidence: 99%
“…This observation also justifies the findings that theories like the mode coupling theory (MCT) and dynamic density functional theory which requires structure as an input cannot predict the difference in the dynamics of two systems having similar structures 7 . However, following these studies, there has been further investigation involving some of us in analyzing the role of pair structure in the dynamics 8,9 . It was shown that although the structure of the system cannot predict the actual dynamics, it has the information of the dynamical transition temperature, often referred to as the mode coupling transition temperature, T c 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…However, following these studies, there has been further investigation involving some of us in analyzing the role of pair structure in the dynamics 8,9 . It was shown that although the structure of the system cannot predict the actual dynamics, it has the information of the dynamical transition temperature, often referred to as the mode coupling transition temperature, T c 8,9 . These studies further showed that the information of the difference in the dynamics of two systems having very similar structure is also embedded in the structure.…”
Section: Introductionmentioning
confidence: 99%